Complete Genome Sequencing of Eight Brucella abortus Biovar 1 Strains Isolated from Water Buffalo - Paradiso, Rubina (Genome Announc, 2018)
Brucellosis is a zoonotic disease caused by bacteria of the genus Brucella. The disease is endemic in many areas, causing chronic infections responsible for reproductive disorders in infected animals. Here, we present eight complete genome assemblies of eight Brucella abortus strains isolated from water buffaloes farmed in the Campania region.